2022
DOI: 10.23887/jisd.v6i1.42894
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Handphone Use on Character Development of Children in Elementary School

Abstract: Uncontrolled use of mobile phones will negatively impact children's development, especially character development. Children who only focus on cellphones, such as playing games and social media, will neglect their responsibilities and discipline. This study aimed to analyze the impact of using mobile phones on the development of children's character at elementary school age, especially in the fifth grade of elementary school, using descriptive qualitative methods. The methods used to collect data are observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…The results of this study revealed no effect of attachment to mobile phones on emotional attachment in the sense of emotional attachment in social reality; they were tied to mobile phones and the person they were connected to but disrupted in social interaction. This study reinforces previous research that revealed excessive use of mobile phones will result in adverse effects, one of which is the inability to socialize (Quratul Ain, 2022).…”
Section: The Effect Of Dependence On Mobile Phones On Aspects Of Ment...supporting
confidence: 90%
“…The results of this study revealed no effect of attachment to mobile phones on emotional attachment in the sense of emotional attachment in social reality; they were tied to mobile phones and the person they were connected to but disrupted in social interaction. This study reinforces previous research that revealed excessive use of mobile phones will result in adverse effects, one of which is the inability to socialize (Quratul Ain, 2022).…”
Section: The Effect Of Dependence On Mobile Phones On Aspects Of Ment...supporting
confidence: 90%